Predictive Finite Element Method for axial crush of composite tubes - Lourenço, Nuno F.S. (2002)
This thesis describes the development of a predictive Finite Element methodology for the crush behaviour and specific energy absorption of composite material tubes. Numerical studies were undertaken based on experimental data for the following composite materials: